Con i frammenti del tempo. Il nuovo Relais San Lorenzo a Bergamo Alta di Adolfo Natalini - Bartocci, Gabriele (Firenze Architettura, 2019)
Adolfo Natalini’s project for the expansion of the San Lorenzo Hotel in Bergamo Alta addresses the subject of the relationship to the ancient, declined in an urban context such as that of the upper city. The architects reflects the features of the place through the interpretation of its constitutive elements proceeding, in the architectural composition, by processes rather than by objects.